1987
DOI: 10.1177/009365087014001006
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Decline of Research on the Diffusion of the News, 1945-1985

Abstract: Research on word-of-mouth diffusion of news, presented initially by media, began in 1945. The Kennedy assassination stimulated numerous studies. However, by the 1970s the pace of such research slowed. At present, the tradition has all but run out. The findings of forty years yield six broad generalizations, but little theory. In view of the vital role of the news in modern society, the decline in this research tradition is difficult to understand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In some cases, interpersonal networks have been shown to be important, while in others they played little, if any, role. The nature of the news event, the time and day on which the event occurs, and social-demographic factors such as age, religion, and social class have all been shown to influence the importance interpersonal networks play in the news diffusion process (DeFleur, 1987).…”
Section: Past Research Into Information Diffusionmentioning
confidence: 99%
“…In some cases, interpersonal networks have been shown to be important, while in others they played little, if any, role. The nature of the news event, the time and day on which the event occurs, and social-demographic factors such as age, religion, and social class have all been shown to influence the importance interpersonal networks play in the news diffusion process (DeFleur, 1987).…”
Section: Past Research Into Information Diffusionmentioning
confidence: 99%
“…However, people often talk to each other about topics of personal interest (DeFleur, 1987;Rogers, 2000), and there is some evidence to suggest that this is the case with the discussion of music and music preferences, too (Rentfrow & Gosling, 2006).…”
Section: Music Preferences Related To Discussionmentioning
confidence: 99%
“…Scholars have found that people tend to discuss things in which they are interested, including media content that they consider personally relevant and important (DeFleur, 1987;Kubey & Peluso, 1990). In a recent study of music-related discussion, Sun, Youn, and Kutaraporn (2006) found that involvement with music was positively and significantly correlated with online chatting.…”
Section: Communication Quarterly 377mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there seem to be fewer class-based barriers for social interaction about public issues, especially those involving dramatic events. For example, there were instantaneous cross-class interactions in the aftermath of the J. F. Kennedy assassination and other major tragedies (DeFleur, 1987;Rosengren, 1973).…”
Section: Now Equation 5 Becomesmentioning
confidence: 99%